Community-Based Utilization of JKN Capitation Funds to Strengthen Food Security Through Primary Health Innovation in Sabang City - Syahferi Anwar; Balqis Nurmauli Damanik; Irwansyah Putra; Nurdina Fitri; Dhea Amanda Putri (Universitas, 2025)
This community service program aimed to improve the capacity of primary health care providers in utilizing JKN capitation funds to support food security efforts in Sabang City. The activity was initiated in response to the limited use of capitation funds for promotive and preventive services, particularly in nutrition and food-related programs. Using a participatory action research (PAR) approach, the intervention involved two primary health centers (Puskesmas) through a series of mentoring sessions, workshops, focus group discussions, and joint action planning. Key outputs included improved understanding of JKN policy frameworks, development of nutrition-oriented budget plans, and the initiation of community food initiatives. Pre- and post-assessments showed a significant increase in participants’ knowledge scores, with an average improvement of 20.5 points. The program also triggered behavioral changes such as collaborative budgeting, active community involvement, and the emergence of local leaders in health and nutrition. These findings highlight the strategic role of JKN capitation funds in promoting community-based food security through primary health services. The intervention model has the potential to be scaled and adapted in other regions with similar contexts to strengthen intersectoral health governance and local resilience in food and nutrition systems